Mavacoxib and meloxicam for canine osteoarthritis: a randomised clinical comparator trial. (20th September 2014) - Walton, M. B.; Cowderoy, E. C.; Wustefeld‐Janssens, B.; Lascelles, B. D. X.; Innes, J. F.
Abstract : NSAIDs are the cornerstone of medical management of canine osteoarthritis (OA). Meloxicam is a daily‐administered NSAID widely available in a liquid formulation and manufacturer's summary of product characteristics (SPC) advise that it is given at the lowest effective dose. Mavacoxib is a long‐acting NSAID given as a monthly tablet. This study compares these drugs in the management of canine OA. In all, 111 dogs with OA of the elbow, hip or stifle were randomly assigned to receive one of these NSAIDs for a 12‐week period, and to administer them as per the manufacturer's SPC. Outcomes, including ground reaction forces and three validated clinical metrology instruments, were measured at baseline, 6 and 12 weeks. Improvements were seen in all outcome measures for both groups to a similar degree, and adverse events occurred at a similar rate. There were significant improvements in outcome measures from week 6 to week 12, as well as from baseline. Long‐term meloxicam dose was more important than recent dose. Clinical efficacy and adverse event rates are similar for meloxicam and mavacoxib when administered as per their UK SPC. This is relevant information for veterinary surgeons when prescribing NSAID treatment for canine OA.